Effect of a silver diamine fluoride and potassium iodide-based desensitizing and cavity cleaning agent on bond strength to dentine. (July 2016) - Koizumi, Hiroyasu; Hamama, Hamdi H.; Burrow, Michael F.
Abstract: Objectives: Recently a silver diamine fluoride and potassium iodide solution (Riva Star, SDI Australia) has been introduced for clinical use as a desensitizing agent or a cavity cleaner. Little is known whether the precipitate produced will affect adhesion to dentin. The aim of this study was to determine whether Riva Star influenced bond strengths to an etch-and-rinse (Optibond FL; Kerr, USA), 2-step self-etching (Clearfil Liner Bond F; Kuraray Noritake Dental, Japan) and all-in-one (Optibond Versa; Kerr) resin-based adhesives and a resin-modified GIC adhesive (Riva Bond LC; SDI Australia). Methods: Human mid-coronal dentin was used; the adhesives were bonded according to the manufacturers׳ instructions or after the dentine surfaces had been treated with the Riva Star. Teeth were sectioned into 1 mm×1 mm samples and subjected to a microtensile bond strength test. Results were analysed using univariate analysis of variance and Tukey HSD test. Results: Adhesive strengths were adversely affected for all adhesives: manufacturer instructions: Optibond FL 32 MPa, SE Bond 28.5 MPa, Optibond Versa 35, Riva Bond LC 18.4 MPa; Riva Star treated groups: Optibond FL 22 MPa, SE Bond 10.9 MPa, Optibond Versa 9.6 MPa, Riva Bond LC 14.5 MPa. Only the GIC and etch-and-rinse adhesive were less effected by the Riva Star application. SEM analysis showed that Riva Star left a precipitate on the dentine surface. Conclusions: It was concluded that if Riva Star is used as a desensitizing and cavity cleaning agent then tooth surfaces should be lightly roughened. Riva Star should not be used as a 'whole cavity' 'disinfecting' agent but may be used for spot application where a cavity floor approximates the pulp where caries-affected dentine may still exist, otherwise adhesion may be compromised.